Pediatric immune-mediated necrotizing myopathy - Wang, Chen-Hua; Liang, Wen-Chen (Frontiers in Neurology, 2023)
Immune-mediated necrotizing myopathy (IMNM) is a type of inflammatory myopathy. Most patients with IMNM produce anti-3-hydroxy-3-methylglutaryl coenzyme A reductase or anti-signal-recognition particle autoantibodies. IMNM is much rarer in children than in adults. We conducted this mini review focusing on pediatric IMNM to present current evidence regarding its epidemiology, clinical characteristics, diagnosis, and treatment. Our findings indicate that pediatric IMNM often causes severe muscle weakness and is refractory to corticosteroids alone. Furthermore, delayed diagnosis is common because of the clinicopathological similarity between IMNM and inherited myopathy. Raising awareness regarding pediatric IMNM may facilitate early diagnosis and effective treatment.